Maize Variety and Population Studies in a Cassava Maize Intercropping System - Arthur, J. (University of Ghana, 1988)
This study was conducted to identify some agronomic characters of maize plants which make them suitable for use in cassava/maize intercropping systems. The feasibility of intercropping cassava with high maize populations was also studied. A strip-split plot design with a parallel-row systematic arrangement in which five maize varieties, IK.84A-2135, IB84A-203 , TZSR-Y-1, 1368 x 5012 and 9450 x 4001 at five population densities of 10,000, 20,000, 40,000, 80,000 and 160.000 plants/ha intercropped within two cassava spacings, 100 x 100cm and 100 x 67cm was used. . Increasing maize population in the mixture from 10,000 tQ 160.000 plants/ha caused a decrease in leaf area, stalk diameter, leaf angle, ear weight, delayed silking, increased ear and plant height, leaf area index, root and stem lodging, barrenness and stover weight of maize. Maize yields peaked at 80.000 plants/ha and declined thereafter. Cassava spacing did no affect maize yields. Correlations between maize yields and agronomic characteristics of the maize varieties were not consistent. Agronomic characteristics of cassava observed at 8 weeks, four months and seven months after planting indicated that maize plant height and maturity had an effect on cassava growth. Cassava plant height and internode length increased whilst stem diameter, number of branches and leaves, root yield and its related components, shoot and root dry weight, and harvest index decreased with increasing intercropped maize population. Land Equivalent Ratio (LER) values indicated that shortness and earliness are desirable agronomic characteristics too be incorporated in maize varieties intended to be used in cassava/maize intercropping. Suggested optimum maize population in the intercrop for IK84A-2135 was 80,000 plants/ha. This population gave the highest LER. At the same range of cassava spacings, 40,000 plants/ha of the other maize varieties could be used.
A Thesis Presented to the Faculty of Agriculture University of Ghana In Partial Fulfilment of the Requirements for the Degree Master of Philosophy (Crop Science) 1988